The governance models of universities: The case of Iran - Somayeh Tohidyan Far; Kurosh Rezaei-Moghaddam; Bruno Dallago (International Journal of Business and Development Studies)
Objective: Due to the importance of the relationship between the state and the university, which indicates the governance model of the university, this paper first determined the characteristics of the different models of university governance and then examined and identified the models of governance of Iranian universities during six development plans. We considered three governance models (state-centered model, Humboldt model, market-oriented model). Methods: Quantitative content analysis was used in order to evaluate the six development plans of Iran regarding different governance model. Results: The results show that the most frequencies for state-centered model presented in the first Development Plan and the most emphasis of Humboldt model was on the fifth Plan. The component frequency of the market-oriented or entrepreneurial governance dimensions in the Iranian development plans indicates that this model was considered for the first time in the third plan and the emphasis on this model in the development plans shows an increasing trend. Conclusions: The estimation of the weighting indicators showed that the emphasis of the development plans on turning to the market-oriented or entrepreneurial model in decision making is increasing, so we suggest that more researcher in their study consider transition toward third-generation universities in Iran as a developing country.